Delivering the promise of your brand, keeping the promise ... and other keys to creating brands people love - Till, Brian 1960- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from The truth about creating brands people love (ISBN: 9780137128167) by Brian D. Till and Donna Heckler. Build a brand that everyone in the organization owns, lives, loves--and shines through in every customer interaction. A brand is a promise you make to your consumers. That promise has two parts: what you say you are promising, and what you actually deliver"--Resource description page.
Keywords: Branding (Marketing); Stratégie de marque; branding